Contributions to the knowledge of Pabstiella (Orchidaceae: Pleurothallidinae) from Brazil: A new species, new synonyms and taxonomic notes - Gutiérrez Morales, Nicolás [UNESP]; de Brito, A.L.V. Toscano; Restrepo, Eugenio; Gil-Amaya, Karen; de Camargo Smidt, Eric [UNESP] (Magnolia Press, 2025)
A new species of Pabstiella native to the southeastern Brazilian Atlantic Rainforest is described and illustrated. The new species is compared with morphologically similar taxa, and its infrageneric placement is inferred based on morphology. In addition, six species are proposed as synonyms: P. dasilvae [= P. fragae], P. discors [=P. garayi], P. isabelae [=P. gossameri], P. melior [=P. brachystele], P. naimekei [=P. ezechiasi] and P. setibensis [=P. savioi]. Respective photographs and taxonomic discussions are provided for each case.
Keywords: Atlantic Rainforest; endemism; epiphyte; Serra do Mar; taxonomy